ANALYSIS OF MARKETING CAPABILITIES, COMPETITIVE ADVANTAGE AND ORGANIZATIONAL CULTURE IN IMPROVING SME PERFORMANCE(SMALL AND MEDIUM ENTERPRISES) - Harmiaty Bahar; Windayani Windayani; Muh. Husriadi; Triwulandari Nehru Putri (PT. Anagata Sembagi Education, 2024)
Small and Medium Enterprises (SMEs) face significant challenges in maintaining performance amidst increasingly tight market competition, especially in utilizing marketing capabilities, competitive advantages, and organizational culture. This study aims to explore the impact of investment in training and technology, participation in industry conferences, and collaboration with technology partners on SME performance. Qualitative research methods were used, including in-depth interviews and thematic analysis, to identify key factors influencing the success of these strategies. The results show that investments in training and technology significantly increase employee competency and technology adoption, while participation in technology conferences and collaborations expands innovation opportunities and market access. The implications of these findings underscore the importance of an integrative approach that combines training, technology and strategic partnerships to enhance the competitiveness and long-term success of SMEs. This research provides new contributions to the SME management literature as well as practical recommendations for industry players and policy makers.